2014
DOI: 10.3164/jcbn.14-24
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between non-labile iron parameters, total carbonyl and malondialdehyde in major thalassemia

Abstract: Thalassemia patients are at high risk of iron-induced toxicity and oxidative stress consequences. The present cross-sectional study is conducted to determine whether or not lipid peroxidation or protein oxidation is correlated with iron parameters in patients with thalassemia major. To prove this hypothesis, malondialdehyde and total carbonyl were correlated with the degree of excess iron concentration in the patients. A total of 118 Arabic Iraqi patients and 30 healthy children were participated in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Conversely, the aberrant production of ROS could randomly attack lipids, proteins, nucleic acids, and carbohydrates, causing cell and tissue damage [ 19 ]. Former studies have 19reported that overproduction of free radicals could induce excessive degeneration of the polyunsaturated lipids, leading to elevated MDA levels [ 3 17 ]. Previous studies have also shown that MDA was a significant indicator to check lipid peroxidation and cellular oxidative damage [ 15 ], and its concentration was positively correlated with the degree of free radical-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the aberrant production of ROS could randomly attack lipids, proteins, nucleic acids, and carbohydrates, causing cell and tissue damage [ 19 ]. Former studies have 19reported that overproduction of free radicals could induce excessive degeneration of the polyunsaturated lipids, leading to elevated MDA levels [ 3 17 ]. Previous studies have also shown that MDA was a significant indicator to check lipid peroxidation and cellular oxidative damage [ 15 ], and its concentration was positively correlated with the degree of free radical-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…Then the results of Tamam, et al, (2012) is supported by the results of the next research that vitamin E supplementation improve erythrocyte fragil-ity and hemoglobin levels in patients with -thalassemia major children. However, AlHakeim, et al (2014) showed the correlation was not statistically significant between Hb with MDA (r = 0.01). In this study showed MDA level decrease after administration of vitamin E not significant different statistically (p> 0.05) except for the group of patients with hemoglobin levels before transfusion 6-8 g/dL decreased MDA level were significant different statistically (p <0.05) for the group of patients with hemoglobin levels before transfusion <6 g/dL had mean Ferritin level higher than Hb level in other groups.…”
Section: Discussionmentioning
confidence: 86%
“…2 Higher levels of serum ferritin (especially over 2500 µg/l) are associated with iron-related organ failure particularly in the liver and heart. 27 This organ damage is not only related to oxidative stress end products, 18 but also to the direct effect of iron overload on the tissues. In the current study, serum CLNK was significantly associated with number of transfusions, ferritin and iron.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous and homozygous condition of β-T yield HbF ranges of 1-5% and 80-100%, respectively. 18 All patients were treated with blood transfusions and received approximately 15 ml of Serological serum CRP was negative in all samples i.e. less than 6mg/L.…”
Section: Subjectsmentioning
confidence: 98%